An exploration of the attitudes and perceptions of the UK public towards self-care for minor ailments. (9th January 2020) - Scott, Ashley; Jones, Colin
Abstract : Aims and objectives: the purpose of this pilot study was to explore the attitudes and perceptions of members of the UK public towards self-care for minor ailments. Background: with an ageing and increasing population, and an NHS under extreme pressure, methods to reduce demand on health services are vital. Increasing the use of self-care for minor ailments is one way in which this pressure could be alleviated. Design and method: this study used qualitative methods including semi-structured telephone interviews. The data were then evaluated, and key themes drawn out using thematic analysis. Findings: the results showed that the public are aware of the notion of self-care, and some are engaging with it. However, for a number of reasons, patients are still likely to want a face-to-face appointment despite the use of online and telephone advice services. Conclusion: the study highlighted that there are multifactorial aspects impacting on a patient's likelihood of engaging in self-care when faced with a minor illness. The results are not generalisable to every member of the public, but interesting questions are raised with regard to the usefulness of current public health messages in various media when there appears to be a lack of desire from the public to use some recommended services.